Exploring EFL Novice Teacher’s Identity Construction: A Narrative Inquiry of Senior High School Teacher - Faisal Abdul Rahman; Eri Kurniawan (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
This study used narrative inquiry to reveal the identity construction process performed by an Indonesian EFL novice teacher through her personal experiences in a senior high school context that is still rarely explored. The interview results revealed that the teacher developed Johnston's framework based on the following three aspects of the teacher's identity: teacher-student relationship, professionalism, and religious beliefs. The results showed that the novice teacher always prioritized academic assistance for students in teacher-student relationships. In terms of professionalism, she saw it as service-oriented. Thus, she always strived to be a better teacher to her students. She also instilled religious values in her English classes. She believed instilling positive values could help socially responsible individuals. It is suggested that future research would use a solid and clear framework regarding the novice teacher's identity construction to make the research process more organized and extend some informative inputs in narrative inquiry research.